Fragile Peace, Handle With Care: Revisiting Character Education and Ethnic Relations in Post-Conflict Sambas Regency, Indonesia - Kurniawan, Syamsul; Miftah, Muhammad; Taufik, Egi Tanadi (Program Studi Pendidikan Agama Islam, 2024)
This qualitative research examined the challenges of the character education for Malay-speaking Muslim children in Sambas Regency, Indonesia, a post-conflict region marked by inter-ethnic tensions. Based on observation, interviews, and literature review, the discussion explored the impact of prolonged ethnic conflict on the education system, character building, and transitional peacemaking. Schools in Sambas faced significant challenges in integrating peace and multicultural education into teaching practices. The discussion illustrated how institutional character education fosters multiculturalism and peace by addressing the residual effects of conflict while aligning with government regulations and local wisdom. It argued that while character education is a long-term effort, it held promise for fostering sustainable positive peace and inter-ethnic harmony. The insights from Sambas offered a framework for character education in similar conflict-affected regions, emphasize the importance of peace and multicultural values in education.